The Role of LBH APIK Jakarta in Legal Protection for Victims of Electronic-Based Sexual Violence - Padmasari, Andin Qanita; Subekti, Subekti (CV. Rayyan Dwi Bharata, 2024)
This research examines electronic-based sexual violence crimes which are regulated in Law Number 12 of 2022 concerning Sexual Violence Crimes and legal protection for KSBE victims by LBH APIK Jakarta. The purpose of this article is to examine the form of legal protection for KSBE victims at LBH APIK Jakarta. The type of research used by the author is empirical legal research or non-doctrinal research. The results of this research state that the legal protection provided by LBH APIK Jakarta is in the field of litigation and non-litigation. In the field of litigation, it begins with assistance at the complaint stage from the victim to LBH APIK Jakarta, reporting to the police, and trial. Meanwhile, in the non-litigation sector, the victim's companion provides protection according to the victim's needs, for example providing legal consultations, assistance (psychological, health and digital security), and subpoenas.